Anaesthetic Priorities In Prehospital Trauma Care: A Paramedic Perspective (The Review of Diabetic Studies, 2025)
Trauma remains a leading cause of mortality and morbidity worldwide, with prehospital care playing a pivotal role in improving survival during the critical “golden hour.” Paramedics are at the forefront of this response, delivering advanced interventions including airway management, analgesia, sedation, hemodynamic stabilization, and rapid transport. This review explores anaesthetic priorities in prehospital trauma care from a paramedic perspective, examining historical evolution, scope of practice variations, legal and ethical considerations, and interprofessional collaboration. Emphasis is placed on airway management strategies, analgesic and sedative choices, and physiologic stabilization, particularly in special trauma populations such as pediatric, geriatric, pregnant, and polytrauma patients. Evidence indicates that paramedics, when adequately trained and supported by structured protocols, can safely perform advanced anaesthetic procedures with outcomes comparable to physician-led teams. Challenges remain regarding skill retention, adverse event prevention, and balancing on-scene interventions with rapid transport. Future directions include innovations in monitoring, telemedicine, new pharmacologic protocols, and expanded critical care paramedic roles. Addressing knowledge gaps through high-quality research is essential to optimize outcomes, standardize practices, and further integrate anaesthetic priorities into global prehospital trauma systems.